2022
DOI: 10.1002/er.8276
|View full text |Cite
|
Sign up to set email alerts
|

Paper‐based flexible membraneless fuel cells using vitamins as both anodic catalyst and fuel

Abstract: Direct liquid fuel cell (DLFC) and membraneless fuel cell using the anode consisting of buckypaper (BP) and vitamin B 12 (Vit B 12 ) (BP/Vit B 12 ) is introduced in physiological condition, while vitamin C (Vit C) is used as anodic fuel. Due to the high sensitivity of Vit B 12 and the inherent feature of BP, the onset potential for the oxidation reaction of Vit C catalyzed by BP/Vit B 12 is À0.1 V (vs Ag/AgCl), and its anodic current density measured at 0.3 V (vs Ag/AgCl) is 1.82 mA cm À2 even in a low Vit C c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…[ 10–12 ] Therefore, EBFCs can use metabolites as fuel selectively that is produced in the human body or sugars contained in the body fluids, and produce electricity without a separate charging process as long as fuel is provided. [ 13–16 ] In addition, EBFCs can be operated under moderate operating conditions, such as body temperature and neutral pH, and has little risk of explosion, making them suitable for use as the power source. [ 17,18 ] Recent studies have already suggested that various types of EBFCs were beyond the level of academic interest, such as catalyst development.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10–12 ] Therefore, EBFCs can use metabolites as fuel selectively that is produced in the human body or sugars contained in the body fluids, and produce electricity without a separate charging process as long as fuel is provided. [ 13–16 ] In addition, EBFCs can be operated under moderate operating conditions, such as body temperature and neutral pH, and has little risk of explosion, making them suitable for use as the power source. [ 17,18 ] Recent studies have already suggested that various types of EBFCs were beyond the level of academic interest, such as catalyst development.…”
Section: Introductionmentioning
confidence: 99%
“…By using enzymes, the EBFC can be operated under milder conditions, such as room temperature (RT) and natural pH, than other conventional fuel cells. Also, metabolites, such as ascorbate, creatine, and lactate, [3][4][5] produced in the body, or saccharides, such as glucose, fructose, and sucrose that are biocompatible materials, can be used as fuel [6,7]. In addi-tion, since enzymes have good fuel selectivity, EBFC can be operated even in conditions of mixed fuel without membrane, and thus, the design flexibility of EBFC is very liberal [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%